Decline in Emergency Department Visits for Acute Gastroenteritis Among Children in 10 US States After Implementation of Rotavirus Vaccination, 2003 to 2013. Issue 7 (July 2016) - Shah, Minesh P.; Tate, Jacqueline E.; Steiner, Claudia A.; Parashar, Umesh D.
Abstract : Background: Rotavirus vaccination of all infants began in the United States in 2006. Although the effect of vaccination on childhood hospitalizations for rotavirus has been well described, the effects of rotavirus vaccine on emergency department (ED) visits are less well documented. Methods: Using the State Emergency Department Databases for 10 US states, we compared the rates of gastroenteritis- and rotavirus-coded ED visits among children <5 years of age in prevaccine (2003 to 2006) with those in postvaccine (2008–2013) years; 2007 was excluded as a transition year. We analyzed ED visit rates by age group, sex, race and rotavirus season. Results: The prevaccine annual gastroenteritis-coded ED visit rate among children <5 years of age of 426 per 10, 000 (annual range, 396–477 per 10, 000) declined to 382 per 10, 000 in postvaccine years, a 10.3% (±0.3%, P < 0.0001) rate reduction overall. Compared with prevaccine years, annual ED visit rates for gastroenteritis decreased by 6.5% (±0.6%) in 2008, 12.3% (±0.6%) in 2010, 14.8% (±0.5%) in 2011, 20.4% (±0.5%) in 2012 and 10.1% (±0.6%) in 2013; a small increase of 1.8% (±0.6%) was seen in 2009 ( P < 0.0001 for all individual comparisons). Declines were similar by sex and race and were greater in children <2 years of age (range 14.1%–20.6%, P < 0.0001) than in older children (increase of 3.3% ±0.6%, P < 0.0001). A decline of 21.2% (±0.4%, P < 0.0001) in ED visits was seen during the rotavirus season months from January through June versus an increase of 9.5% (±0.6%, P < 0.0001) during July to December. ED visits specifically coded for rotavirus showed more prominent declines than for all gastroenteritis. Conclusions: ED visits for gastroenteritis in US children have declined since the introduction of rotavirus vaccine.